Comparative Study of DNA Sequences for Genes Encoding Urease in Klebsiella pneumoniae and Proteus mirabilis - Mohammed Saeed (College of Education for Pure Sciences, 2014)
Abstract Urease genes cluster  consist of  7 genes ureA, ureB, ureC, ureD, ureE, ureF  and ureG. P2 index of Pr. mirabilis genes are 0.429, 0.481, 0.409, 0.378, 0.472, 0.392 and 0.567 for ureA, ureB, ureC, ureD, ureE, ureF and  ureG  respectively and these values are higher compared with 0.323, 0.369, 0.337, 0.226, 0.365, 0.276 and 0.329 for the same genes of K. pneumoniae.Alignment of nucleotide sequences of the two genera showed 58.4%, 36.7%, 26.2%, 67%, 27.8%, 29.7%  and 31.3%  similarity  between ureA, ureB, ureC, ureD, ureE, ureF and ureG respectively, while alignments of amino acids sequences  results in higher values of 81%, 62%, 72.6%, 42%, 39.36%, 42.3% and 77% for the same genes respectively. The threefold, fourfold and sixfold synonymous codons have less incidence of rare codons in Pr. mirabilis so that Ala, Gly, Leu, Thr and Val have no rare codons in their synonymous codons as compared with those in K. pneumoniae